2013
DOI: 10.1371/journal.pone.0062268
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Molecular Mechanisms of Organophosphate and Pyrethroid Resistance in the Fall Armyworm Spodoptera frugiperda

Abstract: The fall armyworm Spodoptera frugiperda is an economically important pest of small grain crops that occurs in all maize growing regions of the Americas. The intensive use of chemical pesticides for its control has led to the selection of resistant populations, however, to date, the molecular mechanisms underlying resistance have not been characterised. In this study the mechanisms involved in the resistance of two S. frugiperda strains collected in Brazil to chlorpyrifos (OP strain) or lambda-cyhalothrin (PYR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
263
2
24

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(294 citation statements)
references
References 39 publications
(52 reference statements)
5
263
2
24
Order By: Relevance
“…Additionally, Carvalho et al. () showed A201S, G227A and F290V alterations in ace1 in S. frugiperda in response to chlorpyrifos. In this study, we found that the majority of specimens tested had the A201S substitution in the ace1 gene, which was also observed by Haddi et al.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Additionally, Carvalho et al. () showed A201S, G227A and F290V alterations in ace1 in S. frugiperda in response to chlorpyrifos. In this study, we found that the majority of specimens tested had the A201S substitution in the ace1 gene, which was also observed by Haddi et al.…”
Section: Discussionmentioning
confidence: 96%
“…Increased metabolic detoxification was involved in OP resistance of Spodoptera frugiperda , where Carvalho et al. () showed increased esterase gene expression possibly conferring resistance to organophosphate insecticides. Increased esterase activity associated with organophosphate resistance has been documented in Drosophila melanogaster (Berrada & Fournier, ), Aonidiella aurantii (Levitin & Cohen, ), Schizaphis graminum (Gao & Zhu, ) and Bemisia tabaci (Zhang et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This species presents management challenges because of its biological and behavioral characteristics and rapid adaptation to chemical control (e.g. resistance to organophosphate and pyrethroid insecticides) [1517]. One alternative to insecticide control has been the use of transgenic hybrids expressing active proteins of the bacterium Bacillus thuringiensis (Bt).…”
Section: Introductionmentioning
confidence: 99%
“…As consideráveis perdas econômicas causadas pela Spodoptera frugiperda faz com que os produtores intensifiquem o uso de inseticidas químicos e consequentemente levem ao desenvolvolvimento da resistência a muitos grupos de inseticidas, tornando o seu controle ainda mais difícil (CARVALHO et al, 2013).…”
Section: Fundamentação Teóricaunclassified